Standing at the threshold : working through liminality in the composition and rhetoric TAship - Macauley, William J.; Anglesey, Leslie R.; Edwards, Brady (Professor of English); Lambrecht, Kathryn M., 1988-; Lovas, Phillip (Logan : Utah State University Press, 2021)
"Articulates identity and role dissonances experienced by composition and rhetoric teaching assistants and reimagines the TAship within a larger professional development process. Current researchers and scholars have not fully explored the liminality of the profession's traditional path to credentialing"--Provided by publisher
Introduction : rhetoric and composition TA observed, observing, observer / by William J. Macauley, Jr. -- Imitation, innovation, and the training of TAs / by Lew Caccia -- Multimodal analysis and the composition TAship : exploring embodied teaching in the writing classroom / by Lillian Campbell and Jaclyn Fiscus-Cannaday -- Disciplinarity, enculturation and teaching identities : how composition and literature TAs respond to TA training / by Jennifer K. Johnson -- The graduate teaching assistant as assistant WPA : navigating the hazards of liminal terrain between the role of "student" and the role of "authority figure" / by Kylee Thacker Maurer and Faith Matzker with Ronda Leathers Dively -- The invisible TA : disclosure, liminality, and repositioning disability within TA programs / by Rachel Donegan -- From imposter to "double agent" : leveraging liminality as expertise / by Kathryn M. Lambrecht -- Beyond "good teacher"/"bad teacher" : generative self-efficacy and the composition and rhetoric TAship / by Megan Schoettler and Elizabeth Saur.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 22, 2021).
JSTOR
Keywords: Graduate teaching assistants; English language -- Rhetoric -- Study and teaching (Higher); Academic writing -- Study and teaching; Assistants d'enseignement.; Écriture savante -- Étude et enseignement; Higher; EDUCATION; Study & Teaching; Academic writing -- Study and teaching; English language -- Rhetoric -- Study and teaching (Higher); Graduate teaching assistants; Electronic books